Household Macronutrient Prices and Livestock Health in Western Kenya - Kappes, Alexander J.; Marsh, Thomas L. (Frontiers in Veterinary Science, 2020)
Understanding food insecurity issues is in part contingent on understanding food consumption and its costs. We develop estimates of protein, lipid, and carbohydrate macronutrient consumption from food consumption in western Kenya. We then calculate the shadow price per gram of macronutrient consumption as a share-weighted expense-consumption ratio. Using household bovine, goat, and sheep livestock health observations we analyze the effect livestock illness has on macronutrient consumption and costs. We find that on average carbohydrates have a 75% budget share, with protein at 14% and lipids at 11%. Average macronutrient shadow prices are 0.0936 Ksh/g for carbohydrates, 0.4373 Ksh/g for protein, and 0.5938 Ksh/g for lipids. Average village-level livestock illness occurrences have significant effects on macronutrient shadow prices. Bovine illness occurrence explains shadow price increases of 0.1113 for protein, 0.121 for lipids, and 0.0341 for carbohydrates. Sheep illness occurrence explains shadow price increases of 0.1405 for protein, 0.182 for lipids, and 0.0455 for carbohydrates. Livestock illness is empirically shown to increase macronutrient shadow prices, and hence the costs of available energy consumption. These results help guide policy seeking to increase balanced nutrient consumption in undernourished areas with smallholder farming systems.